Controlling Iron Versus Oxygen Redox in the Layered Cathode Na0.67Fe0.5Mn0.5O2: Mitigating Voltage and Capacity Fade by Mg Substitution. Issue 30 (26th June 2022) - Boivin, Edouard; House, Robert A.; Marie, John‐Joseph; Bruce, Peter G.
Abstract: Layered oxides for Na‐ion batteries containing Fe have attracted strong interest mainly due to their low cost. However, full oxidation of Fe 3+ to Fe 4+ is rarely seen before O‐redox sets in and is typically accompanied by voltage and capacity fade on cycling. On charging P2‐Na0.67 [Fe0.5 Mn0.5 ]O2, Fe 3+ is oxidized to only ≈ Fe 3.3+ before the onset of O‐redox. O‐redox occurs when the Na content is sufficiently low (Na ≈ 0.3) to permit the transition from P‐type to O‐type stacking, thus enabling Fe 3+ migration to the Na layer. Fe 3+ migration generates cation vacancies in the transition metal layer, forming □‐O‐□ configurations, which trigger the onset of O‐redox. In contrast, doping this material with Mg 2+ to form P2‐Na0.67 [Fe0.25 Mn0.6 Mg0.15 ]O2 allows full oxidation of Fe 3+ to Fe 4+ before the Na content is low enough to favor O‐type stacking. During O‐redox, Mg 2+ is displaced into the Na layers instead of Fe. Mg substitution enables greater reversibility of the Fe 3+ /Fe 4+ redox couple and significantly suppresses Fe migration, which is responsible for the voltage and capacity fade observed for P2‐Na0.67 Fe0.5 Mn0.5 O2 . Abstract : The Fe 3+ /Fe 4+ redox couple in Na‐ion battery cathodes, such as P2‐Na0.67 [Fe0.5 Mn0.5 ]O2, is typically in competition with O‐redox and accompanied by voltage and capacity fade on cycling due to Fe migration. In this article, Mg substitution to form P2‐Na0.67 [Fe0.25 Mn0.6 Mg0.15 ]O2 permits full oxidation of Fe to +4 before O‐redox, preventing Fe migration, and resulting in substantially improved voltage and capacity retention.